Análise das entrevistas de quatro surdocegos adquiridos sobre a importância do guia-intérprete no processo de comunicação e mobilidade - Carillo, Elenir Ferreira Porto (2008)
The present study had as goal analyzing the opinion of the deafblinds acquired on the importance of the guide-interpreter in the process of communication and mobility in routine situations. It is focused specifically, on one hand, in situations that decrease the number of difficulties faced by them and their overcoming of the same ones; and on the other hand, situations that increase difficulties on the way of the deafblind. The sample was constituted by four deafblinds acquired, members of the Brazilian Association of the Deafblinds who already took part in programs of habilitation and rehabilitation related to communication and mobility, and the ones who make use of guide-interpreter services. Data was collected by individual interviews using a questionnaire specially elaborated for this project, organized in charts displaying this way, situations which make possible the decrease, overcoming and increase of the difficulties to each individual studied and the sample as a whole. The data analyzed showed that the guide-interpreter can overcome or decrease the deafblind s difficulties as they use different communication and mobility techniques. It was considered by the individuals researched, the necessity of this professional to have the ability and experience on the application of these techniques. However, the issues related to the deficiency on the application of such techniques by the guide-interpreter were the causes of the increase of difficulties reported by the individuals studied. It was also shown interferences coming from personal issues, pointing out to interpersonal relation issues, something not explored fully on the education of this professional. Attention to this matter could contribute satisfactorily on the performance of the guide-interpreter along with deafblinds acquired.